politicon I. What Constitutionalism? Notes on Paul Blokker’s „New Democracies in Crisis?" - Stambulski, Michał; Muszyński, Karol; Zomerski, Wojciech; Wróbel, Marcin; Czarnota, Adam; Blokker, Paul (Centre for Legal Education and Social Theory (CLEST), 2018)
We would like to present you the first issue of “Politicon. Rule of Law – Constitutionalism – Public Sphere” zine. It contains papers created on the basis of our reading of Paul Blokker’s book “New Democracies in Crisis? A Comparative Constitutional Study of the Czech Republic, Hungary, Poland, Romania and Slovakia”. The book, published in 2014, anticipated the inevitable clash between legal and political constitutionalism. The ongoing alienation of legal constitutionalism and the perception of the constitution as a mere legal act (and not as a political act) in Central and Eastern Europe undermines its social embedding. This opens the door to political questioning of constitutional rules. Politics, excluded from constitution, returns with double force. From the perspective of 2018, this diagnosis seems even more accurate.
Keywords: rule of law; constitutionalism; democracy; Paul Blokker